Dalle applicazioni professionali al 3D per tutti - Santarsiero, Domenico; Florio, Carlo; Ancona, Valerio (GEOmedia, 2008)
From professional applications to 3D for everyone The applications of 3D technology are constantly maturing and so are the solutions designed to satisfy the needs of various professionals. The development of extremely user oriented solutions, which encouraged the use of 3D technology by a wide range of users, have evolved alongside a market in which final user skills are fundamental. The origins of this trend are particularly evident in the massive diffusion of geospatial web applications.